Immunization - The Effect Of Maternal Knowledge And Attitudes On Immunization Coverage - Vishwanathan H; Rohde Jon E (Wolters Kluwer Medknow Publications, 1990)
Three thousand six hundred and twenty four mothers selected from100 villages randomly chosen from 60 UIP districts were interviewed. Mothers of fully immunized children were better educated, of a higher social class and were willing to actively seek immunization than mothers of partially and non-immunized children. The source of information was generally a health facility. The strategy of outreach services would benefit the poor and ill-informed mothers to have their children fully immunized.